2007
DOI: 10.1111/j.1525-1438.2007.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and clinical predictors of lymph node metastases in epithelial ovarian cancer

Abstract: Para-aortic lymphadenectomy is part of staging in early epithelial ovarian cancer (EOC) and could be part of therapy in advanced EOC. However, only a minority of patients receive therapy according to guidelines or have attendance to a specialized unit. We analyzed pattern of lymphatic spread of EOC and evaluated if clinical factors and intraoperative findings reliably could predict lymph node involvement, in order to evaluate if patients could be identified in whom lymphadenectomy could be omitted and who shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 39 publications
5
67
3
4
Order By: Relevance
“…Overall, previous studies reported a rate of ~45-60% nodal involvement in advanced ovarian cancer (2,3,9,14). In the present study, collective nodal metastases were detected in 74.62% of the cases (Table I).…”
Section: Discussionsupporting
confidence: 60%
“…Overall, previous studies reported a rate of ~45-60% nodal involvement in advanced ovarian cancer (2,3,9,14). In the present study, collective nodal metastases were detected in 74.62% of the cases (Table I).…”
Section: Discussionsupporting
confidence: 60%
“…The detection of metastases is positively correlated with the number of lymph nodes removed (11,12). Complete pelvic and paraaortic lymphadenectomy was shown to result in the detection up to 250 or more lymph nodes (9). An overall incidence of lymph node metastasis of approximately 14% was reported in clinical early-stage EOC, with a higher incidence in grade III tumors (20%) and in the serous histologic subtype (23%) than in grade I (4%) and mucinous tumors (3%) (5).…”
mentioning
confidence: 97%
“…Lymphatic metastases of EOC mainly occur in the paraaortic and paracaval lymph nodes, although they can also be found in the pelvic lymph nodes (5)(6)(7)(8)(9)(10). Tumor cells travel along the lymph vessels that accompany the ovarian artery and vein in the suspensory ligament up to the high paraaortic and paracaval regions.…”
mentioning
confidence: 99%
“…≤30% of the patients with apparently early epithelial ovarian cancer might be upstaged after comprehensive surgical staging [3] [4]. Previous reports by Cass et al and Maggioni et al showed that patients with even early ovarian tumor confined to ovary might have pelvic or even Para aortic lymph nodes metastases which making systemic lymphadenectomy improving progression-free survival and disease-free survival [5] [6]. Although advances in diagnosis and management of epithelial ovarian cancer have changed in the last 25 years, the overall survival has not been improved as approximately 65% to 70% of all ovarian cancer continues to be diagnosed with advanced stage (III or IV).…”
Section: Introductionmentioning
confidence: 99%